Features of Gut Microbiome Associated With Responses to Fecal Microbiota Transplantation for Inflammatory Bowel Disease: A Systematic Review - Zhang, Jindong; Guo, Yangyang; Duan, Liping (Frontiers in Medicine, 2022)
Fecal microbiota transplantation (FMT) has been seen as a novel treatment for inflammatory bowel disease (IBD). Results on the microbial alterations and their relationship with treatment efficacy are varied among studies. We performed a systematic review to explore the association between microbial features and therapy outcomes. We searched the PubMed, Web of Science, Embase and Cochrane Library databases from inception to November 2020. Studies investigating efficacy of FMT and baseline microbial features or dynamic alteration of microbiome during FMT were included. The methodological quality of included cohort studies and randomized controlled trials was assessed using Newcastle-Ottawa Scale (NOS) and the Cochrane risk of bias tool, respectively. Thirty studies were included in the analysis. Compared with non-responders, microbial structure of patients who responded to FMT had higher similarity to that of their donors after FMT. Donors of responders and non-responders had different microbial taxa, but the results were inconsistent. After FMT, several beneficial short chain fatty acids – producing taxa, such as Faecalibacterium, Eubacterium, Roseburia and species belonging to them, were enriched in responders, while pathogenic bacteria (Escherichia coli and Escherichia-Shigella) belonging to phylum Proteobacteria were decreased. Alterations of microbial functional gene and metabolites were also observed. In conclusions, response to FMT was associated with gut microbiota and their metabolites. The pre-FMT microbial features of recipients, the comparison of pre- and post-FMT microbiota, and the relationship between recipients and donors at baseline should be further investigated, using uniform and standardized methods.